Energy recovery from sugarcane bagasse under varying microwave-assisted pyrolysis conditions. (December 2022) - Allende, Scarlett; Brodie, Graham; Jacob, Mohan V.
Abstract: Waste management and utilization of waste is a major global issue. This study investigated the influential parameters on the energy recovery from the sugarcane bagasse breakdown under microwave pyrolysis conditions. The by-product yield is optimised from 45 different combinations of microwave power, reaction time and microwave susceptor. The surface methodology, energy efficiency and byproduct quality were studied. Low power, less microwave susceptor and longer residence time are the desirable conditions for high biochar yield due to the gradual thermal decomposition of the biomass and low heating rates. The highest bio-oil yield was obtained from higher microwave power and lower residence time. The excess pyrolysis temperature generated by the higher microwave power and higher microwave susceptor addition produces higher temperatures beyond the optimal condition for bio-oil production. This phenomenon is relative to the self-gasification of the biochar during the high pyrolysis power, contributing to the formation of H2, CO and CH4 . Graphical abstract: Unlabelled Image Highlights: Microwave Assisted Pyrolysis was used to breakdown sugarcane bagasse biomass. By-products exhibits dependence on microwave power, reaction time and susceptor. Biochar yield and properties are affected by the microwave power. Waste to Energy conversion efficiency depends on input microwave power and susceptor. Sugarcane bagasse biomass based biochar can be used for carbon sequestration.